Robust Organic Photosensitizers Immobilized on a Vinylimidazolium Functionalized Support for Singlet Oxygen Generation under Continuous-Flow Conditions - Masuda, Koichiro; Wang, Yao; Onozawa, Shun-ya; Shimada, Shigeru; Koumura, Nagatoshi; Sato, Kazuhiko; Kobayashi, Shū (Synlett, 2020)
Rose Bengal was immobilized on a vinylimidazolium functionalized support, and the heterogeneous organic photosensitizer thus prepared was applied for photooxidation reactions of organic molecules under continuous-flow conditions. Substituents of the cation part of the support were found to play a crucial role in determining the lifetime of the catalyst. More than 11 days continuous operation of a flow reaction was achieved.
Keywords: photooxidation; flow chemistry; organic dye; supported catalyst; Rose Bengal; continuous-flow reaction